SYNTHESIS, MT –QSAR STUDIES FOR PREDICATION OF ANTIMICROBIAL ACTIVITY OF SCHIFF BASES, CARBOHYDRAZIDE AND ANILIDES/AMIDES - MONIKA,; SUCHETA,; RUCHITA,; SHILPA JAIN,; MEENU PALIWAL,; HIMANSHU, (International Journal of Pharma and Bio Sciences, 2015)
In the present investigation, a series of schiff base (1-20), carbohydrazide (31-43) and amides/anilides (21-30/44-56) of nalidixic acid was synthesized in appreciable yield and characterized by physicochemical as well as spectral means. The synthesized compounds were evaluated in vitro for their antimicrobial activity against Gram-positive bacteria S. aureus, B. subtilis, Gram negative bacteria E. coli & fungal strains C. albicans & A. niger by tube dilution method. Antimicrobial activity results indicated that compounds 16, 24, 36, 53 (MIC = 6.25 μg/mL) were the most potent antimicrobial agents. The results of antimicrobial screening also indicated that compounds having NO2, Br, F, Cl, OCH3 substituents were the most active one. mt-QSAR investigation used Hansch analysis was applied to find out correlation between antimicrobial activities with physicochemical properties of synthesized compounds. The mt-QSAR revealed that the antibacterial and antifungal activity of these synthesized derivatives against microorganisms under test was mainly governed by second order molecular connectivity index (2c)and zero order molecular connectivity index (0cv). It also indicated the importance of zero order molecular connectivity index (0cv)in describing the antimicrobial activity of synthesized compounds.